EFFECT OF SODIUM PENTACHLOROPHENATE ON PROTEIN METABOLISM OF THE GASTROPOD, INDOPLANORBIS EXUSTUS - CHAUDHARI, T.R.; PATIL, P.N.; RAO, K.R.; SUBHASH, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1998)
Widely used herbicide, sodium pentachlorophenate has hazardous effects on the non-target animal species. During the present study freshwater gastropod, Indoplan orbis existus is subjected to LC10 and LC50 concentrations for the periods of 24, 48, 72 and 96 hours. It is noted that protein level is depleted while protease activity shown initial increase and then there appeared a marked decrease. The amino acid reserves are found to be decreased and then increased after later periods of exposure. The herbicide stress induced effects are discussed in the light of available literature.